Assessment of dietary exposure to heterocyclic amines based on the Korean total diet study. Issue 3 (4th March 2022) - Lee, Youngsun; Lee, Ki Soo; Kim, Cho-Il; Lee, Jee-Yeon; Kwon, Sung-Ok; Park, Hyun-Mee
ABSTRACT: Heterocyclic amines (HCAs) are contaminants in proteinaceous foods produced by cooking at high temperatures. This study was the first assessment of exposure to HCAs using the Korean total diet study. Twelve HCAs were analysed in 1, 232 pooled samples using six isotope-labelled internal standards and HPLC-MS/MS. The daily intake of HCAs in the Korean population was estimated based on the concentration of HCAs in the total diet study samples and individual food consumption data from the Korean National Health and Nutrition Examination Survey. Among HCAs, the intake of β-carbolines, such as harman and norharman, was the highest, followed by the intake of PhIP. The primary sources of HCA intake were meat, fish, shellfish, and beverages, including alcohol. The margin of exposure to PhIP was 2, 349, 000 at the average level and 373, 000 at the 95 th percentile in the Korean population. The estimated daily intake of all HCAs in the Korean population was considered safe.